Evidence for a causal relationship between low vitamin D, high BMI, and pediatric-onset MS. (25th April 2017) - Gianfrancesco, Milena A.; Stridh, Pernilla; Rhead, Brooke; Shao, Xiaorong; Xu, Edison; Graves, Jennifer S.; Chitnis, Tanuja; Waldman, Amy; Lotze, Timothy; Schreiner, Teri; Belman, Anita; Greenberg, Benjamin; et al.
Abstract : Objective: To utilize Mendelian randomization to estimate the causal association between low serum vitamin D concentrations, increased body mass index (BMI), and pediatric-onset multiple sclerosis (MS) using genetic risk scores (GRS). Methods: We constructed an instrumental variable for vitamin D (vitD GRS) by computing a GRS for 3 genetic variants associated with levels of 25(OH)D in serum using the estimated effect of each risk variant. A BMI GRS was also created that incorporates the cumulative effect of 97 variants associated with BMI. Participants included non-Hispanic white individuals recruited from over 15 sites across the United States (n = 394 cases, 10, 875 controls) and Sweden (n = 175 cases, 5, 376 controls; total n = 16, 820). Results: Meta-analysis findings demonstrated that a vitD GRS associated with increasing levels of 25(OH)D in serum decreased the odds of pediatric-onset MS (odds ratio [OR] 0.72, 95% confidence interval [CI] 0.55, 0.94; p = 0.02) after controlling for sex, genetic ancestry, HLA-DRB1*15:01, and over 100 non–human leukocyte antigen MS risk variants. A significant association between BMI GRS and pediatric disease onset was also demonstrated (OR 1.17, 95% CI 1.05, 1.30; p = 0.01) after adjusting for covariates. Estimates for each GRS were unchanged when considered together in a multivariable model. Conclusions: We provide evidence supporting independent and causal effects of decreased vitamin D levels and increased BMI on susceptibility to pediatric-onset MS.